Strategi pengembangan pariwisata dalam meningkatkan perekonomian daerah kabupaten Subang - Nidaan Khofiya; Salsha Awalia (Post Graduate School of Government Science, 2025)
Subang Regency is a region that has quite large tourism potential, facing challenges in developing the tourism sector to improve the local economy. The natural beauty, cultural sites, and rich traditions in the Subang Regency area have great potential to support economic growth, but suboptimal management hampers this potential. Therefore, it is important to formulate a tourism development strategy that can lead to improving the regional economy. This study aims to analyze tourism development strategies that can improve the regional economy of Subang Regency, by highlighting the potential, challenges, and solutions that can be applied. The method used in this study is a qualitative approach with a case study technique. Data were obtained through interviews with stakeholders, document analysis, and direct observation at several tourist attractions in Subang Regency. The data analysis technique used is a SWOT analysis to evaluate the strengths, weaknesses, opportunities, and threats in tourism development. The results of the study show that Subang Regency has quite large tourism potential, especially in the natural and cultural tourism sectors. However, there are several challenges, such as lack of infrastructure, low quality of human resources in the tourism sector, and less than optimal tourism promotion. The recommended strategies include improving the quality of infrastructure, training for tourism industry players, and strengthening regional promotion through digital media and cooperation with travel agents.